The mediating role of service quality in customer value and brand experience impact on repurchase intention - Nurfakih, Shafa Ajeng Wulandari; Subagiana, IGM; Saputra, Upayana Wiguna Eka; Waelan, Waelan; Rangkuti, Agus Edy (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2024)
Understanding the impact of customer value and brand experience on repurchase intention, while optimizing service quality, is essential for ensuring sustainable business performance. This study examines the mediating role of service quality in the influence of customer value and brand experience on repurchase intention at PTNJM Bali Head Office. The research aims to determine the direct and indirect effects of customer value and brand experience on repurchase intention, considering service quality as a potential mediator. This study employs an explanatory research design with a quantitative approach. Data were collected from 100 respondents using questionnaires, observations, and interviews. A non-probability sampling method with purposive sampling was applied to ensure relevant participants. The collected data were analysed using SPSS Version 29 and Smart PLS Version 3 to assess the relationships among variables and the mediation effects of service quality. The analysis revealed that customer value does not have a positive and significant effect on repurchase intention, while brand experience positively and significantly influences repurchase intention. Additionally, service quality has a direct positive and significant impact on repurchase intention. However, the findings indicate that service quality does not mediate the relationship between customer value and repurchase intention, nor does it mediate the relationship between brand experience and repurchase intention. These findings suggest that while brand experience and service quality are critical factors in encouraging repurchase behaviour, customer value alone does not directly contribute to repeat purchases. Furthermore, service quality does not serve as an effective mediator in strengthening the impact of customer value and brand experience on repurchase intention. These insights provide valuable implications for businesses, highlighting the importance of enhancing brand experience and service quality to foster customer loyalty and long-term retention.